2008
DOI: 10.1259/bjr/11877313
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentation of sarcoidosis of the breast

Abstract: We report a case of sarcoidosis with an unusual radiological appearance. The patient was a 41-year-old asymptomatic woman who presented for a baseline screening mammogram, which revealed an asymmetric, slightly increased density in the upper outer quadrant of her left breast. Ultrasonography failed to demonstrate any mass. Her past medical history was remarkable for sarcoidosis. Stereotactic core biopsy revealed sarcoidosis diffusely infiltrating the breast parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…In most cases of breast sarcoidosis, patients are highly likely to have subclinical pulmonary disease or other organ involvement. Pulmonary function testing, serum lysozyme and serum ACE levels are helpful in assessing activity of the disease, and directing therapy 35 36. In the current series, none of the patients had any history or systemic evidence of sarcoidosis.…”
Section: Discussionmentioning
confidence: 71%
“…In most cases of breast sarcoidosis, patients are highly likely to have subclinical pulmonary disease or other organ involvement. Pulmonary function testing, serum lysozyme and serum ACE levels are helpful in assessing activity of the disease, and directing therapy 35 36. In the current series, none of the patients had any history or systemic evidence of sarcoidosis.…”
Section: Discussionmentioning
confidence: 71%
“…Primary breast sarcoidosis is a very rare manifestation, accounting for less than 1% of patients with sarcoidosis. 7 A case series review of 35 cases of primary sarcoidosis showed that only 20% (7 cases) presented as a breast mass and only 3% (1 case) had a bilateral breast masses with mainstay treatment being steroids and if required, surgical intervention. 8 Wegener granulomatosis of breast or granulomatous angitis of the breast is another rare entity, which can mimic IGM, with an incidence of 1 in 20,000 to 30,000.…”
Section: Discussionmentioning
confidence: 99%
“…The mammographic abnormality is typically a mass, asymmetry, or an area of architectural distortion 33,34. Mammographic and ultrasonographic features are usually worrisome for malignancy.…”
Section: Systemic Inflammatory Diseasementioning
confidence: 99%